EDUKASI PEMANFAATAN KECERDASAN BUATAN (AI) YANG BERTANGGUNG JAWAB DALAM MENDUKUNG KUALITAS PEMBELAJARAN - Pasya Fahira Hutasuhut; Stevany Veronica Dobberd; Dwi Sekar Ningrum; Joice Florencia; Miko Dwi Aprianto; Rian Farta Wijaya (Cattleya Darmaya Fortuna, 2025)
The rapid development of Artificial Intelligence (AI) has significantly transformed learning processes by providing fast access to information, personalized learning support, and assistance in completing academic tasks. However, the improper and excessive use of AI may lead to overdependence, reduced critical thinking skills, and ethical issues in academic practices. This community service activity aims to enhance the literacy and awareness of students and educators regarding the responsible use of AI to support learning quality. The implementation methods include socialization sessions, training workshops, interactive discussions, and hands-on assistance in utilizing AI as an ethical and proportional learning support tool. The program materials cover fundamental AI concepts, opportunities and risks of AI usage in education, academic integrity, and strategies for using AI to improve learning outcomes without diminishing learner autonomy. The results indicate a significant improvement in participants’ understanding of the appropriate functions and limitations of AI in the learning process, as well as the development of more critical and responsible attitudes toward the use of AI. This activity is expected to contribute to the creation of a healthy, ethical, and sustainable digital learning ecosystem in the era of technology-driven educational transformation.